Corrosion Rate Analysis of JIS G-3141 Steel for Automotive Inner Wheel House Production with Weight Loss Method - Arwati, I Gusti Ayu; Ifani, Febrina (Chemical Engineering Department, Engineering Faculty, Universitas Sultan Ageng Tirtayasa, 2022)
The growth of car sales and production has decreased since 2020, this is due to corrosion of automotive steel plates in the form of low carbon steel stored in warehouses. The purpose of this study was to obtain the value of the corrosion rate and its effect on mechanical properties and changes in the composition of carbon values. Low carbon steel plates commonly used by automotives where the material is low carbon steel JIS G-3141, with its elemental content of C 0.12%, Mn 0.5%, P 0.04% and S 0.045% with tensile mechanical properties. strength 270 N/mm2, elongation 37%. The purpose of this study was to obtain the value of the corrosion rate and its effect on mechanical properties and changes in the composition of carbon values. Low carbon steel plates commonly used by automotives where the material is low carbon steel JIS G-3141, with its elemental content of C 0.12%, Mn 0.5%, P 0.04% and S 0.045% with tensile mechanical properties. strength 270 N/mm2, elongation 37%.